DESIGN AND DEVELOPMENT OF ACCOUNTING INFORMATION SYSTEM FOR CASH SALES OF MILD STEEL - Ari Puspita; Yuyun Yuningsih; Muhammad Fahmi; Rahmat Tri Yunandar (Jurnal Riset Informatika, 2021)
Technological developments are now experiencing very rapid development, so many entrepreneurs are competing to produce new companies. At this time the light steel business is growing rapidly. Researchers try to make research on the cash sales system of mild steel sales, most companies do not yet have a computerized recording system, so that the invoice input process is hampered, as well as sales notes that are still written manually, and sometimes errors still occur in reading the names and quantities of goods. ordered, so the report generation will take a long time. As a form of solving the problems encountered by researchers, a computerized financial recording system is better than a manual system.Sales System, Cash Sales System, Information System